Development of Interactive Multimedia Integrating Problem-Based Learning - Muhammad Syarkin (Yayasan Darussalam Bengkulu, 2026)
Mathematics learning in elementary education continues to present significant challenges, particularly in fraction concepts that require young learners to transition from concrete experiences toward abstract relational understanding. This study aimed to develop and evaluate an interactive multimedia learning product integrating Problem-Based Learning (PBL) and Banjar ethnomathematics to improve second-grade elementary students’ mathematics learning outcomes in fraction learning. The study employed a Research and Development (R&D) approach using the ADDIE instructional design model, encompassing analysis, design, development, implementation, and evaluation phases. Data were collected through teacher interviews, teacher and student needs analysis questionnaires, expert validation sheets, teacher and student practicality questionnaires, and learning outcome assessments covering cognitive, affective, and psychomotor domains. Expert validation involved three validators representing content, instructional media, and classroom practice expertise. The developed multimedia demonstrated strong overall validity (92.75%) and high practicality based on teacher (91.11%) and student (84.60%) evaluations. Reliability analysis indicated acceptable to excellent internal consistency across the evaluation instruments (Cronbach’s alpha = 0.716–0.925). Effectiveness testing using a paired-samples t-test revealed a statistically significant improvement in students’ cognitive learning outcomes, with mean scores increasing from 14.7 (pretest) to 23.7 (posttest), t(167) = -33.2, p < .001, with a very large effect size (Cohen’s d = 2.56). Complementary findings also indicated positive affective (M = 8.14) and psychomotor (M = 11.93) learning outcomes. These findings suggest that the intentional integration of interactive multimedia, scaffolded problem-based pedagogy, and culturally contextualized Banjar ethnomathematics can create an effective, engaging, and contextually meaningful instructional environment for supporting elementary fraction learning